2022
DOI: 10.21037/atm-22-2469
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends of peroral endoscopic myotomy during 2010–2022: a bibliometric analysis

Abstract: Background: Peroral endoscopic myotomy (POEM) has been rapidly accepted as a safe and effective therapy for achalasia and other esophageal motility disorders, and has inspired novel submucosal tunneling techniques. This study analyzed the trends in POEM research and compared contributions from different countries, regions, institutions, journals, and authors using bibliometric analysis to predict the trends and potential hotspots in POEM research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…be able to facilitate knowledge creation (8,9) The recently published report by Dr. Liu et al, "Publication trends of peroral endoscopic myotomy during 2010-2022: a bibliometric analysis" reviewed the data and compared contributions between countries, regions, institutions, journals, and authors (10). Bibliometric analysis of publications on achalasia was based on the databases Scopus.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…be able to facilitate knowledge creation (8,9) The recently published report by Dr. Liu et al, "Publication trends of peroral endoscopic myotomy during 2010-2022: a bibliometric analysis" reviewed the data and compared contributions between countries, regions, institutions, journals, and authors (10). Bibliometric analysis of publications on achalasia was based on the databases Scopus.…”
Section: Editorialmentioning
confidence: 99%
“…As a result, researches from the United States were the most common (n=743) and were pivotal influence (n=743), followed by research from China (n=346) and Japan 43 (n=223). Dr. Inoue and his colleagues were the most active researcher and Showa university (Japan) was the most active institution in the field of POEM research (10).…”
Section: Editorialmentioning
confidence: 99%
“…Endoscopic resection procedures, initially developed in Japan to treat superficial gastrointestinal lesions, are now performed worldwide [1]. Despite their minimally invasive nature, these procedures pose significant challenges, particularly for less experienced endoscopists, due to their technical complexity and lengthy duration.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on POEM treatment for achalasia patients have been reported during this period. However, up to now, there has been no comprehensive and objective bibliometric visualization analysis on POEM in treating achalasia, except for two articles that analyzed achalasia [7] and POEM [8], respectively. Bibliometric analysis, introduced by Alan Pritchard in 1969 [9], is a scientific quantitative analysis method of published studies that integrates philology, mathematics, and statistics.…”
mentioning
confidence: 99%